Fair competition for an evolving economy - Keldon Bester (Centre for International Governance Innovation (CIGI), 2023)
Fair competition is essential to economic growth. Without it, corporate concentration takes over. Canada's permissive merger law has allowed a small number of big corporations to dominate key sectors of the Canadian economy, resulting in limited consumer choice. Although Canada's competition laws are currently under review, its global peers are taking steps to protect competition in their own economies. This paper recommends that Canada should focus on the role of fair competition in its competition law framework, specifically differentiating beneficial and harmful competition. Canada's abuse of dominance provision protects against anti-competitive conduct, but it does little to protect new and emerging competitors. This paper suggests that Canada should look to international peers such as the European Union, Germany and the United States for cues to reform its own system.
Keywords: 330